2000
DOI: 10.1007/s004419900158
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E gene expression correlates with endogenous lipid nutrition and yolk syncytial layer lipoprotein synthesis during fish development

Abstract: During embryogenesis of teleost fish, the formation of a yolk syncytial layer (YSL) enables the resorption of the yolk reserves and development up to the larval stage. We have examined the changes of the yolk cell structure in relation to yolk and oil-globule lipid utilization during development of the turbot (Scophthalmus maximus). After encapsulation by the YSL, resorption of the single, large oil globule occurred predominantly after yolk resorption and was slower in fasting larvae. The YSL was in contact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 77 publications
(89 reference statements)
2
60
0
1
Order By: Relevance
“…1B, arrow), similar to other apolipoproteins that have been reported in fish (Babin et al, 1997;Poupard et al, 2000;Xia et al, 2008). YSL is a layer consisting of a membrane-enclosed group of nuclei on top of the yolk cells and beneath the blastoderm cells.…”
Section: Expression Pattern Of Apoc1 During Embryogenesis In Zebrafishsupporting
confidence: 68%
“…1B, arrow), similar to other apolipoproteins that have been reported in fish (Babin et al, 1997;Poupard et al, 2000;Xia et al, 2008). YSL is a layer consisting of a membrane-enclosed group of nuclei on top of the yolk cells and beneath the blastoderm cells.…”
Section: Expression Pattern Of Apoc1 During Embryogenesis In Zebrafishsupporting
confidence: 68%
“…Apo E expression correlated with endogenous lipid nutrition and lipoprotein synthesis during development of turbot (Poupard et al, 2000).…”
Section: Absorptionmentioning
confidence: 96%
“…During the period from fertilization to mouth opening, the embryos and prefeeding larvae use endogenous yolk nutrients previously stored in the yolk globules, hyaloplasm, and oil globules (Poupard et al 2000). In the past decade, many attempts have been undertaken on the biochemical composition of egg yolk components and their digestion, synthesis and transformation during embryonic development of teleosts (Henderson and Tocher 1987;Heming and Buddington 1988;Rønnestad and Fyhn 1993;Wiegand 1996;Poupard et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, many attempts have been undertaken on the biochemical composition of egg yolk components and their digestion, synthesis and transformation during embryonic development of teleosts (Henderson and Tocher 1987;Heming and Buddington 1988;Rønnestad and Fyhn 1993;Wiegand 1996;Poupard et al 2000). A large amount of data revealed that the formation of a YSL (yolk syncytial layer), a structure unique to teleosts, enables the resorption of the yolk reserves and development to the larval stage (Manfredi Romanini et al 1969;Walzer and Schönenberger 1979a;Shimizu and Yamada 1980;Cousin et al 1987;Sire et al 1994;Mani-Ponset et al 1996;Babin et al 1997;Poupard et al 2000). However, the developmental behavior of genes that control the utilization of yolk reserves is virtually unknown (Poupard et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation